Case Report: Developed Infraocular Squamous Cell Carcinoma and Nasal Basal Cell Carcinoma in Xeroderma Pigmentosum - Icha Aisyah; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2018)
Introduction: Xeroderma pigmentosum (XP) is a rare autosomal recessive disease caused by a gene defect in nucleotide excision pathway named nucleotide excision repair (NER), characterized by photosensitivity of the skin. Case: A 5 year old girl, 15 kgs, came with brown and black spots on the entire body since she was 7 month old. These complaints were accompanied with itchiness and burning sensation. Since two years ago, a small bump appeared on the nose and below the left eye, increasingly enlarged, also easily bled. She complained red and watery eyes since two weeks ago. Patient often felt glare. Physical examination all over the body found obtained multiple hypopigmented and hyperpigmented macules unsharply marginated with varying size from pinpoint to few cm and also dry skin. Right and left opthalmic region showed red, watery eye, and photophobia. Nasal region showed nodules about 1 cm in size, accompanied by erosion and crusting. Histopathology examination result of left infraoculi region was malignant squamous cell carcinoma and nasal region was malignant basal cell carcinoma. Patient were diagnosed with XP with infraocular squamous cell carcinoma and nasal basal cell carcinoma. Patient was treated with natrium fusidic 2% cream, sunscreen with sun protecting factor (SPF) 30, moisturizer, chlorpheniramine maleate, chemotherapy, and also educated to avoid sun exposure. Discussion: XP causes a variety of clinical manifestations, often with a skin malignancies. Skin biopsy is mandatory to establish the diagnosis